THE IDEOLOGICAL SOURCES OF EUROPEAN LAW: THEIR TYPES AND AXIOLOGICAL NATURE - Melenko, Serhiy (Yuriy Fedkovych Chernivtsi National University, 2017)
The article under discussion deals with the problem of determining the ideological sources of European law in the context of various philosophical and legal methodologies, their axiological contents being the primary aspect of investigation. The article also traces out the phenomenology of these methodologies’ formation, as well as the process of European law transition from the category of ideological notion to the sphere of normative regulation of social relations. The peculiarities of the above- mentioned process and its extrapolation on the state of the present-day European legislature (the latter possessing certain direct international-legal regulatory contents) have been investigated in the article as well.
Види та аксіологічна природа світоглядних джерел європейського права
Keywords: European law, international law, Ancient Greek philosophy, philosophy of law, ethical values, the European Convention of Human Rights and Fundamental Freedoms, Magna Carta.